Development of a thermostabilised multiplex lamp-ict-dna biosensor for rapid detection of entamoeba histolytica and non-pathogenic entamoeba species - Chong , Foo Phiaw (2017)
Entamoeba histolytica is the only pathogenic Entamoeba species that can cause severe invasive intestinal amoebiasis in humans. Approximately 10% of the world population is estimated to be infected, in which 100,000 deaths were reported annually in endemic countries. New diagnostic assays are needed to distinguish E. histolytica from its nonpathogenic morphologically identical Entamoeba species, Entamoeba dispar and Entamoeba moshkovskii, as routine microscopy method is labour-intensive, requires highly skilled microscopist, low in sensitivity and unable to distinguish E. histolytica from its nonpathogenic species. Other detection methods such as biochemical assays and antibody as well as antigen detection techniques are either time-consuming and/or cold-chain dependent. Loop-mediated isothermal amplification (LAMP) that features single temperature amplification has created an opportunity to develop point-of-care assays. Thus, the present study aimed to formulate a dry-reagent triplex LAMP mix for detection of E. histolytica, Entamoeba spp. and the incorporated internal amplification control as well as to develop a nonhybridisation-based NALFIA biosensor for detection of the LAMP amplicons. Two sets of specific primers targeting E. histolytica and Entamoeba spp. were designed based on E. histolytica serine-rich protein (SREHP) gene and E. histolytica large subunit ribosomal RNA gene, respectively. In addition, a set of primers was designed and incorporated into multiplex LAMP to serve as an internal amplification control to rule out false negative result. The triplex LAMP assay was designed to produce double-labelled double-stranded amplicons with 60 min of incubation at 63°C followed by termination at 80°C for 5 min. These double-labelled amplicons were captured by NALFIA biosensor through specific affinity interaction between capture proteins with haptens on the reaction pad. The fluorescein labelled on each of the amplicons then immobilised fluorescein antibody conjugated gold nanoparticles, and aggregation of gold nanoparticles formed red/pinkish lines which were visualised with naked eye within 15 min. Development of triplex LAMP assay not only reduced the amplification time, it also eliminated the necessity of having thermal cycler which was costly and required trained personnel to operate. Besides, having NALFIA biosensor as amplicons analyser obviated the need for agarose gel electrophoresis which was time-consuming and utilised hazardous chemicals. The triplex LAMP-NALFIA assay that was developed in dry-reagent form was a cold-chain-free and ready-to-use diagnostic test. The detection limit of the assay was 10 E. histolytica trophozoites whereas the specificity was 100% when tested with 71 non-Entamoeba microorganism. The dry-reagent triplex LAMP mix and NALFIA biosensor had an estimated shelf-life of at least 181 days based on heat stability test conducted at 37°C. Development of the dry-reagent triplex LAMP mix coupled with a NALFIA biosensor had effectively simplified the molecular detection of E. histolytica and the nonpathogenic Entamoeba species.